Expanding India’s Maritime Strategy: A Critical Analysis of RELOS and the Northern Sea Route Opportunity - Pradeep Sabar; Munu Meher (Journal of Innovation in Education and Social Research, 2025)
The 2025 signing of the Reciprocal Exchange of Logistics Support (RELOS) agreement between India and Russia marks an important shift in India’s maritime strategy. Earlier focused mainly on the Indian Ocean and Indo-Pacific, India is now expanding its strategic interest toward the Arctic region. Through RELOS, India can use Russian logistics facilities, including those in the Arctic and Far East, giving India potential access to the Northern Sea Route (NSR), a shorter and emerging shipping route between Asia and Europe. This paper examines how RELOS strengthens India’s naval operations, energy security, trade routes, and Arctic engagement. It also highlights key challenges such as harsh environmental conditions, limited technology, and rising geopolitical competition in the Arctic.